(untitled) (International conference on multidisciplinary science, 2025)
Privatization of state-owned enterprises (SOEs) is a significant economic reform that impacts state budget revenues in both the short and long term. This article explores the financial implications of privatization, highlighting how the sale of SOEs generates immediate revenue that can reduce public debt or fund strategic investments. It also examines the long-term effects, including the potential loss of direct income from profitable enterprises and the gains from increased tax revenues through improved efficiency, economic growth, and private sector innovation. Challenges such as undervaluation of assets, misuse of privatization proceeds, and regulatory failures are analyzed, along with strategies to maximize the fiscal benefits of privatization. By adopting transparent processes, leveraging proceeds for long-term investments, and implementing robust regulatory frameworks, governments can ensure that privatization contributes to fiscal sustainability and economic development. The article draws on examples from countries such as the United Kingdom, Russia, and India to illustrate the varied outcomes of privatization programs.